The Effects of Zanzalacht on the Gonotrophic cycle of the Adult House fly Musca Domestica - Radwan E H; Youssef N S; Hashem H O; Shalaby A M (Journal of Plant and Animal Ecology, 2019)
Melia azedarach extract were applied by feeding the adult female flies on diets mixed with the extracts at different doses. The concentrations of Melia azedarach utilized were 1.8, 2.4 and 3.6%. The gonotrophic cycles of length of 90, 753, 67.6 and 84, 72, 68 hours were obtained after feeding at age 24 hours with diet mixed with doses of 1.8, 2.4 and 3.6% fruit extract; respectively. 98 & 96 hours were the length of gonotrophic cycle in the control groups. The length of 86.7, 72.3, 57.3 and 89.3, 75, 61 hours were obtained after feeding adults at age 48 hours with diets mixed with different doses of fruit extract of the same plant 97.3 and 98.7 hours were the length of the control groups. Proportions of the egg hatching reached 69, 55.3, 49 and 72.9, 64.2, 52 in groups of eggs obtained from 24 hours adults feeding with diets mixed with doses of 1.8, 2.4 and 3.6% fruit extract; respectively. Also 68.7, 53.3,48 5 and 81 2, 70, 56.3 were the proportions of egg hatching obtained from groups at age 48 hours after feeding with diets mixed with the same doses. 85, 77.6, 62.2 and 92.6, 88.9, 84.9 were the proportions of the egg hatching obtained from groups feeding with diets mixed with doses of 1.8, 2.4 and 3.6% fruit extract of Melia azedarach; respectively. The pupae showed larval-pupal intermediates which failed to complete the pupal period and died after emerging from the third larval instar.
Keywords: Melia Azedarach